2004
DOI: 10.1080/0049825041008962
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics ofS-3-(4-acetylamino-phenoxy)-2-hydroxy-2-methyl-N-(4-nitro- 3-trifluoromethyl-phenyl)-propionamide in rats, a non-steroidal selective androgen receptor modulator

Abstract: S-3-(4-acetylamino-phenoxy)-2-hydroxy-2-methyl-N-(4-nitro-3-trifluoromethyl-phenyl)-propionamide (also known as S-4) is a non-steroidal selective androgen receptor modulator demonstrating tissue-selective androgenic and anabolic effects. The purpose of the present study was to examine the systemic pharmacokinetics, elimination and oral bioavailability of S-4 in rats.2. Thirty-five male Sprague-Dawley rats weighing approximately 250 g were randomly assigned to one of seven treatment groups. Intravenous doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Pharmacokinetic studies of S4 in rats (Kearbey et al, 2004) determined the lack of parent drug in the urine, thus suggesting extensive metabolism, and the more recent in vitro metabolism studies with several enzyme preparations revealed deacetylation, amide hydrolysis, A-ring nitro-reduction, and hydroxylation of aromatic rings as the major phase-I pathways in humans (Gao et al, 2006). In that study, microsomal enzymes were observed to contribute to deacetylation reaction, cytosolic enzymes to hydrolysis, and the role of CYP3A4 enzymes as one of the major phase-I enzymes to catalyze deacetylation, hydrolysis, and oxidative reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies of S4 in rats (Kearbey et al, 2004) determined the lack of parent drug in the urine, thus suggesting extensive metabolism, and the more recent in vitro metabolism studies with several enzyme preparations revealed deacetylation, amide hydrolysis, A-ring nitro-reduction, and hydroxylation of aromatic rings as the major phase-I pathways in humans (Gao et al, 2006). In that study, microsomal enzymes were observed to contribute to deacetylation reaction, cytosolic enzymes to hydrolysis, and the role of CYP3A4 enzymes as one of the major phase-I enzymes to catalyze deacetylation, hydrolysis, and oxidative reactions.…”
Section: Discussionmentioning
confidence: 99%
“…10), was developed using the nonsteroidal androgen antagonist bicalutamide as the lead compound (Gao et al, 2005). Pharmacokinetics studies demonstrated that S-4 is rapidly absorbed, slowly cleared, and has a moderate volume of distribution in rats (Kearbey et al, 2004). S-4 also showed in vivo both 740 androgenic and anabolic activity that is tissue selective.…”
Section: Selective Androgen Receptor Modulatorsmentioning
confidence: 99%
“…Therefore, unlike steroidal analogs, low-affinity plasma protein binding to albumin is unlikely to compete significantly with high-affinity target tissue binding sites. In addition, we performed in vivo studies with a number of compounds, with similar chemical structures demonstrating their favorably pharmacokinetic and pharmacodynamic properties (Yin et al, 2003a;Kearbey et al, 2004;Gao et al, 2005) suggesting that S-26 will be efficacious in vivo.…”
Section: Discussionmentioning
confidence: 99%